Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5530/ijper.51.3s.6
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activities of Piper nigrum L. Against Mastitis Pathogens and its Antioxidant Activities

Abstract: Objective / Purpose: Bacteria causes one of the most common types of chronic mastitis. The most common causative organisms of mastitis include: Staphylococci, Streptococci and coliforms. The scope of this work was to research the antibacterial effects of Piper nigrum extracts against mastitis pathogens, and its antioxidant capacity. Materials and Methods: In our study, 2 Staphylococcus aureus and 5 Coagulase Negative Staphylococcus were used for experiments. Additionally, Piper nigrum were collected from Mugla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
4
19
0
1
Order By: Relevance
“…The observed effect of aqueous extract from cyclamen tubers on this bacterium suggests its potential application as a natural antimicrobial agent in milk products. This result is in accordance with studies of Okmen and coworkers who determined the effect of Cyclamen mirable tubers against S. aureus and fi ve coagulase-negative staphylococci (Okmen et al, 2014). The aqueous extract of wild cyclamen tubers showed stronger effect on B. cereus in comparison to antibiotic penicillin.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The observed effect of aqueous extract from cyclamen tubers on this bacterium suggests its potential application as a natural antimicrobial agent in milk products. This result is in accordance with studies of Okmen and coworkers who determined the effect of Cyclamen mirable tubers against S. aureus and fi ve coagulase-negative staphylococci (Okmen et al, 2014). The aqueous extract of wild cyclamen tubers showed stronger effect on B. cereus in comparison to antibiotic penicillin.…”
Section: Resultssupporting
confidence: 92%
“…tubers showed cytotoxic, spermicidal and antimicrobial activities in vitro (Speroni et al, 2007). Analgesic, anti-intiinfl ammatory, antimicrobial and antioxidative activities of some Cyclamen species such as C. repandum, C. mirabile and C. graecum have been reported as well (Speroni et al, 2007;Calis et al, 1997;Okmen et al, 2014;Metin et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…This antibacterial activity is due to the fact that the leaves of Trigonella foenum-graecum are rich in a wide variety of secondary metabolites such as glycosides, alkaloids, phytosterols, proteins, saponins and phytosterols which have been found in vitro to have antimicrobial properties [69]. The results of Crocus sativus are very similar to those found by Muzaffar in 2016, of the extracts of Crocus sativus against Proteus vulgaris, Klebsiella pneumoniae , Pseudomonas aeruginosa, Staphylococcus aureus and Escherishia coli, with a zone of inhibition of 8mm, 6mm, 9mm, 7mm, and 6mm , respectively [72], and also by Okmen in 2016, when aqueous extract of Crocus sativus showed a maximum inhibition zone against Coagulase-Negative Staphylococci (d=11 mm) [73] The antibacterial activity of Cymbopogon citratus extract is somewhat lower, since it is active only against three bacteria (Escherichia coli , Pseudomonas sp, Enterococcus faecalis) and inactive against Citrobacter freundii and Staphylococcus aureus. Bearing, These results remain interesting, since the diameters of the inhibition zones obtained are very close to the other studies, Zulfa et al in 2016, found that Cymbopogon citratus extracts has an antimicrobial activity against the foodborne pathogens; Bacillus cereus, Escherishia coli, K.pneumonia, and Staphylococcus aureus [74], Moreover, Ewansiha and all also confirmed that the Cymbopogon citratus chloroform leaf extracts showed an intermediate antimicrobial activity against Staphylococcus aureus, Salmonella typhi and Escherishia coli [75].…”
Section: B Discussionsupporting
confidence: 86%
“…According to traditional medicine, some species from the Cyclamen genus were used because of their biological activities [1,2] such as: cytotoxic, spermicidal, antimicrobial [1], laxative, abortive, sedative, purgative, emmenagogue and anti-helmintic [2]. Analgesic, anti-inflammatory, antimicrobial and antioxidative activities of some Cyclamen species such as Cyclamen repandum, Cyclamen mirabile and Cyclamen graecum have also been reported [1,[3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%